2014
DOI: 10.1007/s10549-014-2846-5
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder and arm morbidity in sentinel node-negative breast cancer patients: a systematic review

Abstract: The purpose of this study was to assess which shoulder and arm impairments are common in sentinel node-negative breast cancer patients and to describe the incidence and time course of these impairments. A systematic literature search was performed using different electronic databases until October 2013. Inclusion criteria were (1) research studies that included breast cancer patients surgically treated using the sentinel lymph node biopsy (SLNB) technique, (2) sentinel node-negative patients, and (3) studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 33 publications
8
68
0
3
Order By: Relevance
“…We have observed that 15% of subjects showed clinically significant limitations in shoulder motion at the time of testing. Despite the heterogeneity of our sample, this is consistent with the time-course of arm morbidity reported in women with sentinel node-negative breast cancer [4]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have observed that 15% of subjects showed clinically significant limitations in shoulder motion at the time of testing. Despite the heterogeneity of our sample, this is consistent with the time-course of arm morbidity reported in women with sentinel node-negative breast cancer [4]. …”
Section: Discussionsupporting
confidence: 88%
“…Shoulder motion impairments, including decreased range of motion (ROM), are common following surgery for breast cancer and can cause significant disability that can linger for years following treatment [24]. Symptoms that can limit shoulder motion, such as disuse, pain, numbness, and decreased strength, start to appear within days after cancer surgery and the percentage of patients that suffer from these symptoms tends to increase with time [4]. After the second week post-surgery more than 40% of patients showed a reduction in shoulder abduction of at least 10 degrees [5], and 37% of patients showed a reduction in shoulder flexion of at least 10 degrees [6].…”
Section: Introductionmentioning
confidence: 99%
“…A deeper facet of the relationships between AM and negative affect was revealed when placed in the context of the time course of AM in the immediate years following treatment. Results from the repeated measures ANOVA showed that the greatest degree of severity of restriction in ROM (shoulder abduction and external rotation) was observed in the first year post-surgery, consistent with other longitudinal studies of AM (e.g., [64]). For shoulder abduction, the degree of restriction seen 2 years post-surgery was also significantly greater than that observed 5 years later.…”
Section: Discussionsupporting
confidence: 87%
“…For patients with early-stage breast cancer who have clinically negative axillary lymph nodes, SLNB is a method for staging the axilla that is associated with less morbidity than axillary lymph node dissection (ALND) [4][5][6][7][8][9][10]. Currently, SLNB for breast cancer is usually performed using a radiocolloid method and/or a blue dye method [11].…”
Section: Introductionmentioning
confidence: 99%